'Damned Good Amateurs': Yugoslav Partisans in the Belgrade Operation 1944. Issue 2 (2nd April 2016) - Trifković, Gaj
ABSTRACT: On 16 October 2014, Russian President Vladimir Putin attended a parade in Belgrade marking the 70th anniversary of its liberation by the Red Army and the Communist-led Yugoslav Partisans. In addition to being a public display of the historic bonds and mutual friendship between the two states, the event also symbolically reaffirmed the role of the Yugoslav Partisans in these operations by parading their old battle flags. In light of strong revisionist tendencies in the past 25 years that sought to diminish or even deny the Partisans' contribution to the liberation of the country, this represents a small but important gesture. The aim of this article will be to provide an overview of operations in Serbia from late September to late October 1944, to quantify the Partisans' contribution to the campaign, and to briefly discuss Soviet-Yugoslav cooperation during this period.